Effect of heat treatment on the spheroidisation process - Liew, Cindy Xue Fang. (2011)
When pearlite is subjected to heat treatment for prolong period of time, spheroidization will occurred. Different carbon content and heat treatment time will result in different spheroidization rate and thus having different microstructure. This report investigates and shows how the rate of spheroidization will affect the pearlite